Cathode active materials for solid-state rechargeable batteries

A cathode active material with controlled atomic ratios of lithium, nickel, manganese, and cobalt, combined with fluorine and carbon, and produced through controlled heating, addresses the issues of low retention and high leakage in solid-state batteries, enhancing electrochemical performance.

JP2025500471AActive Publication Date: 2025-01-09UMICORE(BE)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024538189
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-12-21
Publication Date
2025-01-09
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Existing cathode active materials for solid-state batteries exhibit low retention and high leakage capacity, particularly when containing fluorine and being prepared by methods that involve high-temperature heating with polyvinylidene fluoride (PVDF), leading to suboptimal electrochemical performance.

Method used

A positive electrode active material for solid-state batteries is formulated with specific atomic ratios of lithium, nickel, manganese, and cobalt, along with fluorine and carbon, within defined ranges, and is produced by mixing a lithium transition metal-based oxide compound with an F-containing polymer and heating the mixture below 350°C in an oxidizing atmosphere.

Benefits of technology

The solution results in a cathode active material with improved electrochemical properties, demonstrating lower total leakage capacity and higher retention, suitable for solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500471000001
    Figure 2025500471000001
  • Figure 2025500471000002
    Figure 2025500471000002
  • Figure 2025500471000003
    Figure 2025500471000003
Patent Text Reader

Abstract

The present invention relates to a cathode active material for a solid state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that it further comprises fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis, and carbon, the carbon content being ≧370 ppm and ≦5000 ppm as determined by a carbon analyzer, based on the total weight of the cathode active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cathode active material for a solid-state rechargeable battery. More specifically, the present invention relates to a cathode active material containing F atoms for a solid-state battery, preferably the solid-state battery is a polymer-based solid-state battery. The present invention also relates to a method for producing the cathode active material. Furthermore, the present invention relates to a solid-state battery containing the cathode active material. [Background technology]

[0002] The present invention relates to the use of a single crystal positive electrode active material powder containing F for solid-state rechargeable batteries.

[0003] Such a cathode active material comprising the elements aluminum and fluorine on the surface layer is already known, for example from WO 2016 / 116862 (Al), which discloses an F-containing cathode active material, in which F is introduced into the cathode active material by mixing a lithium transition metal oxide with polyvinylidene fluoride (PVDF) and then heating at 375° C. The cathode active material prepared according to this method showed low retention when applied in an electrochemical cell. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2016 / 116862 Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, an object of the present invention is to provide a positive electrode active material having good electrochemical properties.

[0006] A further object of the present invention is to provide a method for producing the positive electrode active material.

[0007] A further object of the present invention is to provide a positive electrode active material obtained by the method.

[0008] A further object of the present invention is to provide a solid-state battery including the positive electrode active material.

[0009] A further object of the present invention is to provide a use of the cathode active material in a solid-state battery.

[0010] A further object of the present invention is to provide a use of said solid-state battery. [Means for solving the problem]

[0011] The object is achieved by providing a cathode active material for a solid-state battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that the cathode active material further comprises: fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis; and carbon, the carbon content being ≧370 ppm and ≦5000 ppm, relative to the total weight of the cathode active material, as determined by a carbon analyzer.

[0012] As shown by the examples and supported by the results shown in Table 2, a lower total leakage capacity (Q total ) and high retention is indeed observed.

[0013] A further aspect of the present invention is a method for producing a cathode active material, comprising sequential steps of mixing a lithium transition metal oxide compound with an F-containing polymer, and heating the mixture at a temperature below 350° C. in an oxidizing atmosphere in a furnace for a period of 1 hour to 20 hours to obtain the cathode active material.

[0014] A further aspect of the present invention is a positive electrode active material obtainable by the method.

[0015] A further aspect of the invention is a solid-state rechargeable battery that includes the positive electrode active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Unless otherwise defined, all terms used in the disclosure of the present invention, including technical and scientific terms, have the meanings commonly understood by those skilled in the art to which the present invention belongs. For further guidance, definitions of terms are included to better understand the teachings of the present invention. As used herein, the following terms have the following meanings: The term "ppm" as used herein means parts per million by mass.

[0017] As used herein, "about" referring to a measurable value such as a parameter, amount, length of time, and the like, is meant to encompass a variation of no more than ±20%, preferably no more than ±10%, more preferably no more than ±5%, even more preferably no more than ±1%, and even more preferably no more than ±0.1% from the specified value, provided such variations are appropriate for the practice of the disclosed invention, although it is to be understood that the value to which the "about" modifier refers is itself specifically disclosed.

[0018] The term "comprising" as used in the present specification and claims should not be interpreted as being limited to the means recited thereafter, and does not exclude other elements or steps. It should be interpreted as specifying the presence of the mentioned features, integers, steps, or components as mentioned, but does not exclude the presence or addition of one or more other features, integers, steps, or components, or groups thereof. Thus, the scope of the expression "a composition comprising components A and B" should not be limited to a composition consisting of components A and B only. It means that in the context of the present invention, the only relevant components of the composition are A and B. Thus, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".

[0019] "Positive electrode active material" is defined as a material that is electrochemically active in the positive electrode. An active material is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a period of time.

[0020] In the following detailed description, preferred embodiments are described to enable the practice of the invention. The invention will be described with reference to these specific preferred embodiments, but it will be understood that the following examples are intended to further clarify the invention and are not intended to limit the scope of the invention. The invention includes numerous alternatives, modifications, and equivalents that will be apparent from consideration of the following detailed description.

[0021] positive electrode active material In a first aspect, the present invention achieves this by providing a cathode active material for a solid state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that the cathode active material further comprises: fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis; and carbon, the carbon content being ≧370 ppm and ≦5000 ppm, based on the total weight of the cathode active material, as determined by a carbon analyzer.

[0022] In a particular preferred embodiment, this is achieved by providing a positive electrode active material for the solid state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that the positive electrode active material further comprises: fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis; and carbon, the carbon content being ≧370 ppm and ≦5000 ppm as determined by a carbon analyzer, relative to the total weight of the positive electrode active material.

[0023] Preferably, the cathode active material comprises fluorine in an amount of at least 0.05 mol%, preferably at least 0.2 mol%, more preferably at least 0.5 mol%, and most preferably at least 0.7 mol%, based on the total atomic content of Ni, Mn, Co in the material, as determined by Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). Preferably, the cathode active material comprises fluorine in an amount of at most 3.0 mol%, preferably at most 2.5 mol%, more preferably at most 2.0 mol%, and most preferably at most 1.8 mol%, based on the total atomic content of Ni, Mn, Co in the material, as determined by ICP-OES. Preferably, the cathode active material comprises fluorine in an amount of 0.05 mol % to 3.0 mol %, preferably 0.2 mol % to 2.5 mol %, more preferably 0.5 mol % to 2.0 mol %, and most preferably 0.7 mol % to 1.8 mol %, as determined by ICP-OES.

[0024] Preferably, the cathode active material comprises aluminum in an amount of at least 0.01 mol%, preferably at least 0.05 mol%, more preferably at least 0.1 mol%, and most preferably at least 0.2 mol%, based on the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES. Preferably, the cathode active material comprises aluminum in an amount of at most 2.0 mol%, preferably at most 1.5 mol%, more preferably at most 1.0 mol%, and most preferably at most 0.8 mol%, based on the total atomic content of Ni, Mn, and Co in the particles, as determined by ICP-OES. Preferably, the cathode active material comprises aluminum in an amount of 0.01 mol% to 2.0 mol%, preferably 0.05 mol% to 1.5 mol%, more preferably 0.1 mol% to 1.0 mol%, and most preferably 0.2 mol% to 0.8 mol%, based on the total atomic content of Ni, Mn, and Co in the particles, as determined by ICP-OES.

[0025] In a preferred embodiment, the cathode active material has an atomic content of nickel of 55.0 mol % or more and 95.0 mol % or less, preferably 58.0 mol % or more and 90.0 mol % or less, and more preferably 60.0 mol % or more and 88.0 mol % or less, based on the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

[0026] In a highly preferred embodiment, the cathode active material has an atomic content of nickel of 55.0 mol % to 75.0 mol %, preferably 60.0 mol % to 70.0 mol %, more preferably 61.0 mol % to 68.0 mol %, based on the total atomic content of Ni, Mn, and Co in the material.

[0027] In a highly preferred embodiment, the cathode active material has an atomic content of nickel of 75.0 mol % or more and 95.0 mol % or less, preferably 78.0 mol % or more and 90.0 mol % or less, more preferably 80.0 mol % or more and 88.0 mol % or less, based on the total atomic content of Ni, Mn, and Co in the material.

[0028] In a preferred embodiment, the cathode active material has an atomic content of cobalt of 0 mol % or more and 40.0 mol % or less, preferably 2.0 mol % or more and 20.0 mol % or less, more preferably 3.0 mol % or more and 18.0 mol % or less, and most preferably 4.0 mol % or more and 10.0 mol % or less, relative to the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

[0029] In a preferred embodiment, the material has an atomic content of manganese of 0 mol % to 40.0 mol %, preferably 2.0 mol % to 30.0 mol %, more preferably 3.0 mol % to 25.0 mol %, and most preferably 4.0 mol % to 10.0 mol %, relative to the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

[0030] As will be understood by those skilled in the art, the amounts of Li, Ni, Mn, Co, F, and Al are measured by ICP-OES. For example, and without limiting the present invention, an Agilent ICP 720-ES is used in the ICP-OES analysis. In the framework of the present invention, the "atomic content" of a given element, which expresses a concentration, means what percentage of the total atoms in the compound are atoms of that element. The notation mol% is equivalent to "molar percent" or "atomic percent". For example, and without limiting the present invention, the XPS analysis is performed using a Thermo K-α+ spectrometer (Thermo Scientific).

[0031] In a preferred embodiment, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at least 0.1, more preferably at least 0.15, and most preferably at least 0.2, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at most 2.5, more preferably at most 2.0, and most preferably at most 1.8, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at least 0.1 and at most 2.5, preferably at least 0.15 and at most 2.0, and most preferably at least 0.2 and at most 1.8, as determined by XPS analysis.

[0032] In a highly preferred embodiment, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at least 0.1, more preferably at least 0.15, and most preferably at least 0.2, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at most 0.8, more preferably at most 0.7, and most preferably at most 0.6, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of at least 0.1 and at most 0.8, preferably at least 0.15 and at most 0.7, and most preferably at most 0.15 and at most 0.6, as determined by XPS analysis.

[0033] In a preferred embodiment, the cathode active material comprises aluminum and has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at least 0.2, preferably at least 0.4, more preferably at least 0.5, and most preferably at least 0.6, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at most 4.0, preferably at most 3.0, more preferably at most 2.0, and most preferably at most 1.5, as determined by XPS analysis. Preferably, the cathode active material has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at least 0.2 to at most 4.0, preferably at least 0.4 to at most 3.0, more preferably at least 0.5 to at most 2.0, and most preferably at least 0.6 to at most 1.5.

[0034] In a highly preferred embodiment, the active cathode material comprises aluminum and has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at least 0.2, preferably at least 0.5, more preferably at least 0.7, and most preferably at least 0.9, as determined by XPS analysis. Preferably, the active cathode material has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at most 1.35, preferably at most 1.30, more preferably at most 1.25, and most preferably at most 1.20, as determined by XPS analysis. Preferably, the active cathode material has an atomic ratio of Al to the total amount of Ni, Mn, and / or Co of at least 0.2 to at most 1.35, preferably at least 0.5 to at most 1.30, more preferably at most 0.7 to at most 1.25, and most preferably at most 0.9 to at most 1.20, as determined by XPS analysis.

[0035] In a preferred embodiment, the active cathode material has an Al to F ratio of at least 1.9, preferably at least 3, more preferably at least 4, where Al has an atomic ratio to the total amount of Ni, Mn, and / or C, as determined by XPS analysis, and F has an atomic ratio to the total amount of Ni, Mn, and / or Co, as determined by XPS analysis. In a preferred embodiment, the active cathode material has an Al to F ratio of at most 10, preferably at most 8, more preferably at most 6, where Al has an atomic ratio to the total amount of Ni, Mn, and / or C, as determined by XPS analysis, and F has an atomic ratio to the total amount of Ni, Mn, and / or Co, as determined by XPS analysis. In a preferred embodiment, the positive electrode active material has an Al to F ratio of ≧1.9 and ≦10, preferably ≧3 and ≦8, more preferably ≧4 and ≦6, where Al has an atomic ratio relative to the total amount of Ni, Mn, and / or C as determined by XPS analysis, and F has an atomic ratio relative to the total amount of Ni, Mn, and / or Co as determined by XPS analysis.

[0036] XPS analysis provides the atomic content of an element in the top layer of a particle with a penetration depth of about 10 nm from the periphery of the particle. The periphery of the particle is also called the "surface". In the framework of the present invention, atomic % means atomic percentage. Atomic % or "atomic percent" as a concentration expression of a given element means what percentage of all atoms in the compound are atoms of that element. The term atomic % is synonymous with mol % or "mole percent". For example, and without limiting the present invention, XPS analysis is performed using a Thermo K-α+ spectrometer (Thermo Scientific).

[0037] In a preferred embodiment, the cathode active material comprises a carbon content of at least 500 ppm of the total weight of the cathode active material, more preferably at least 600 ppm, and most preferably at least 700 ppm of the total weight of the cathode active material, as determined by a carbon analyzer. Preferably, the cathode active material comprises a carbon content of at most 3000 ppm of the total weight of the cathode active material, more preferably at most 2000 ppm, and most preferably at most 1500 ppm of the total weight of the cathode active material, as determined by a carbon analyzer. Preferably, the cathode active material comprises a carbon content of 500 ppm to 3000 ppm, preferably 600 ppm to 2000 ppm, and more preferably 700 ppm to 1500 ppm of the total weight of the cathode active material. As will be appreciated by those skilled in the art, the carbon content of the cathode active material of the present invention is measured by a carbon analyzer. For example, and not by way of limitation, the carbon content can be measured using a Horiba Emia-Expert carbon / sulfur analyzer.

[0038] In a preferred embodiment, the positive electrode material has a median particle size (d50 or D50) of 2.0 μm to 10.0 μm as determined by laser diffraction. For example, and not by way of limitation, the median particle size (d50 or D50) can be measured using a Malvern Mastersizer 3000. Preferably, the median particle size is 2.0 μm to 9.0 μm, more preferably 3.0 μm to 8.0 μm.

[0039] In a preferred embodiment, the positive electrode active material is a single crystal powder, or, in an equally preferred embodiment, the positive electrode active material is a polycrystalline powder.

[0040] The concept of single crystal powder is well known in the art of cathode active materials. It relates to powders with predominantly single crystalline particles. Such powders are a separate type of powder compared to polycrystalline powders made from particles that are predominantly polycrystalline. Those skilled in the art can easily distinguish between these two classes of powders based on microscopic images.

[0041] Single crystal particles are also known in the art as monolithic particles, integral particles or / and monocrystalline particles.

[0042] A technical definition of a single crystal powder is not necessary since such powders can be readily recognized by one skilled in the art using an SEM, however, in the context of the present invention, a single crystal powder may be considered to be defined as a powder in which 80% or more of the particles by number are single crystal particles. This means a powder having a size of at least 45 μm by at least 60 μm (i.e., at least 2700 μm 2 ), preferably at least 100 μm×100 μm (i.e., at least 10,000 μm 2 ) on an SEM image with a field of view.

[0043] A single crystal particle is a particle that is an individual crystal or is formed from less than five, preferably a maximum of three, primary particles that are themselves individual crystals. This can be observed by observing the grain boundaries with a suitable microscopic technique, such as a Scanning Electron Microscope (SEM). Thus, as will be appreciated by those skilled in the art, the determination of the secondary particle median diameter D50 is also applicable to single crystal powders.

[0044] In determining whether a particle is a single crystal particle, grains having a maximum linear dimension observed by SEM that is smaller than 20% of the powder's median diameter D50 as determined by laser diffraction are ignored. This avoids inadvertently considering particles that are essentially single crystal but have some very small other grains, e.g., polycrystalline coatings deposited on them, as not being single crystal particles.

[0045] As will be appreciated by those skilled in the art, polycrystalline powders consist of secondary particles that include a plurality of primary particles, preferably greater than 20 primary particles, preferably greater than 10 primary particles, and most preferably greater than 5 primary particles.

[0046] In certain preferred embodiments, the cathode active material comprises single crystal particles and has a median particle size D50 of 2.0 μm to 10.0 μm, preferably 2.0 μm to 9.0 μm, and more preferably 3.0 μm to 8.0 μm, as determined by laser diffraction, according to the invention.

[0047] In certain preferred embodiments, the cathode active material comprises polycrystalline particles and has a median particle size D50 of 2.0 μm to 10.0 μm, preferably 2.0 μm to 9.0 μm, and more preferably 3.0 μm to 8.0 μm, as determined by laser diffraction, according to the invention.

[0048] In a preferred embodiment, the fluorine source is an F-containing polymer, preferably an F-containing organic polymer, preferably polyvinylidene fluoride, or polytetrafluoroethylene (PTFE).

[0049] In a preferred embodiment, the fluorine-containing organic polymer is heated at a temperature of 200° C. to 350° C., preferably 250° C. to 300° C., for a period of 1 hour to 20 hours to obtain the positive electrode active material.

[0050] In a preferred embodiment, the positive electrode active material is a low leakage positive electrode active material.

[0051] In a further aspect, the present invention provides a secondary particle-based cathode active material for a solid state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that it further comprises fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis, and carbon, the carbon content being ≧370 ppm and ≦5000 ppm relative to the total weight of the cathode active material as determined by a carbon analyzer.

[0052] In a highly preferred embodiment of the secondary particle-based positive electrode active material, all of the embodiments relating to the positive electrode active material according to the first aspect of the present invention apply mutatis mutandis to the secondary particle-based positive electrode active material, for example, the various embodiments relating to the identities and amounts of Li, M', F, and Al described herein in the context of the positive electrode active material are equally applicable to the secondary particle-based positive electrode active material.

[0053] In a further aspect, the present invention provides a single crystal particle based cathode active material for a solid state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, characterized in that it further comprises fluorine, the atomic ratio of F to the total amount of Ni, Mn, and / or Co being ≧0.05 and ≦3.0 as determined by XPS analysis, and carbon, the carbon content being ≧370 ppm and ≦5000 ppm based on the total weight of the cathode active material as determined by a carbon analyzer.

[0054] In a highly preferred embodiment of the single-crystal particle-based positive electrode active material, all of the embodiments relating to the positive electrode active material according to the first aspect of the present invention apply mutatis mutandis to the single-crystal particle-based positive electrode active material, for example, the various embodiments relating to the identities and amounts of Li, M', F, and Al described herein in the context of the positive electrode active material are equally applicable to the secondary particle-based positive electrode active material.

[0055] Manufacturing method In a second aspect, the present invention also includes a method for producing a cathode active material, the method comprising the steps of mixing a lithium transition metal based oxide compound, an F-containing polymer, and optionally an aluminum-containing powder, and heating the mixture at a temperature below 350° C. in an oxidizing atmosphere in a furnace for a time period of 1 hour to 20 hours to obtain the cathode active material.

[0056] A highly preferred embodiment is a method of making an active cathode material, the active cathode material being according to the first aspect of the invention.

[0057] In a preferred embodiment of the method, the lithium transition metal based oxide compound comprises Li, M' and oxygen, where M' comprises Ni, Mn, and Co.

[0058] In certain preferred embodiments, the lithium transition metal based oxides used are also typically prepared according to a lithiation process, i.e., a process in which a mixture of a transition metal oxide precursor and a lithium source is heated at a temperature of preferably at least 500° C. and up to 1000° C. Typically, the transition metal precursor is prepared by co-precipitation of one or more transition metal sources, such as salts, preferably sulfates or nitrates, more preferably sulfates, with the elements Ni, Mn, and / or Co, in the presence of an alkali compound, such as an alkali hydroxide, e.g., sodium hydroxide and / or ammonia. Preferably, the lithium source is metallic lithium or a lithium salt, preferably a lithium salt, such as LiOH.

[0059] In a preferred embodiment, the aluminum-containing powder comprises AI2O3.

[0060] Preferably, the F-containing polymer is an F-containing organic polymer, preferably polyvinylidene fluoride or polytetrafluoroethylene.

[0061] Preferably, the temperature of the mixture is 200°C or more and 350°C or less, preferably 250°C or more and 300°C or less.

[0062] In certain preferred embodiments, the mixture is heated for a period of more than 2 hours, preferably more than 3 hours, more preferably more than 4 hours. In preferred embodiments, the mixture is heated for a period of less than 15 hours, preferably less than 12 hours, preferably less than 10 hours. In preferred embodiments, the mixture is heated for a period of at least 2 hours and not more than 15 hours, preferably at least 3 hours and not more than 12 hours, more preferably at least 4 hours and not more than 10 hours.

[0063] A preferred embodiment of the method is to heat the mixture, and the oxidizing atmosphere comprises or consists of oxygen, such as air.

[0064] Positive electrode active material obtained by this method In a third aspect, the present invention provides a cathode active material obtainable by the method according to the second aspect of the present invention.

[0065] As will be appreciated by those skilled in the art, all embodiments relating to the positive electrode active material according to the first aspect of the invention and / or the method according to the second aspect of the invention apply mutatis mutandis to a positive electrode active material obtainable by the method according to the invention. For example, the various embodiments relating to the identities and amounts of F, Al, Ni, Mn, and Co described herein in the context of a positive electrode active material are equally applicable to a positive electrode active material obtainable by the method for the preparation of a positive electrode active material.

[0066] battery In a fourth aspect, the present invention relates to a battery comprising an active cathode material according to the first aspect of the invention and / or the third aspect of the invention.

[0067] In a preferred embodiment, the battery is a solid-state battery. Preferably, the solid-state battery comprises a polymer-based electrolyte. Preferably, the electrolyte is a polyethylene oxide-based solid electrolyte, more preferably, the electrolyte comprises polyethylene oxide.

[0068] Preferably, the solid-state battery further comprises an anode comprising an active anode material. Suitable electrochemically active anode materials are known in the art. For example, the anode may comprise graphitic carbon, metallic lithium, such as lithium foil, or a metal alloy containing lithium, such as a Li-In alloy, as the active anode material.

[0069] In a preferred embodiment, the battery according to the invention comprises an active cathode material that is a polycrystalline material having a retention of at least 87%, preferably at least 88%, and most preferably at least 89%. Alternatively, in an equally preferred embodiment, the battery according to the invention comprises an active cathode material that is a monocrystalline material having a retention of at least 98%, more preferably at least 99%, and most preferably at least 100%. As will be appreciated by those skilled in the art, battery retention is measured as described under section 1.3.2 of the Examples.

[0070] In certain preferred embodiments, the retention is

number

[0071] Step 1) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V, followed by a 10 minute rest.

[0072] Step 2) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0 V, followed by a 10 minute rest. The discharge capacity of this step is DQ1.

[0073] Step 3) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V.

[0074] Step 4) Switch to constant voltage mode and maintain 4.4V for 60 hours.

[0075] Step 5) Discharge in constant current mode at a C rate of 0.05 with a termination condition of 3.0 V. The discharge capacity of this step is DQ2.

[0076] In a preferred embodiment, the battery according to the invention has a Q of less than 78 mAh / g, preferably less than 75 mAh / g, more preferably less than 70 mAh / g. total Alternatively, in an equally preferred embodiment, the battery according to the present invention comprises a positive electrode active material that is a polycrystalline material having a Q of less than 70 mAh / g, preferably less than 45 mAh / g, more preferably less than 40 mAh / g, even more preferably less than 32 mAh / g, and most preferably less than 32 mAh / g. total As will be appreciated by those skilled in the art, the Q of the battery total is measured as described under Example section 1.3.2.

[0077] In certain preferred embodiments, Q total is preferably defined as the total leakage capacity at high voltage and temperature. In certain more preferred embodiments, Q total is defined as the total leakage capacitance at high voltage and high temperature in step 4) of the test method described below, and preferably, Q total is defined by the Coin Cell Test Procedure in coin-shaped polymer cells cycled at 80° C. using a Toscat-3100 computer-controlled constant current cycling station (Toyo Systems) using a 1C current definition of 160 mA / g in the metal window range of ≧3.0 V / Li and ≦4.4 V / Li according to the following schedule:

[0078] Step 1) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V, followed by a 10 minute rest.

[0079] Step 2) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0 V, followed by a 10 minute rest. The discharge capacity of this step is DQ1.

[0080] Step 3) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V.

[0081] Step 4) Switch to constant voltage mode and maintain 4.4V for 60 hours.

[0082] use In a fourth aspect, the present invention provides the use of an active cathode material according to the first aspect of the invention and / or the third aspect of the invention in a battery.

[0083] A preferred embodiment is the use of the positive electrode active material in a battery, preferably a solid-state battery, more preferably a polymer solid-state battery, to increase the retention of the battery.

[0084] A preferred embodiment is the use of the positive electrode active material in a battery, preferably a solid-state battery, more preferably a sulfide solid-state battery, to reduce leakage of the battery.

[0085] In a fifth aspect, the present invention relates to the use of a battery according to the present invention in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle or a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle. [Example]

[0086] 1. Description of analysis method 1.1.Inductively Coupled Plasma The composition of the positive electrode active material powder is measured by Inductively Coupled Plasma (ICP) method using an Agilent 720 ICP-OES. One gram of powder sample is dissolved in 50 mL of high purity hydrochloric acid (at least 37 wt% HCl with respect to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with a watch glass and heated on a hot plate at 380°C until the powder is completely dissolved. After cooling to room temperature, the solution from the Erlenmeyer flask is poured into a first 250 mL volumetric flask. Then, the first volumetric flask is filled to the 250 mL mark with deionized water, followed by a complete homogenization procedure (first dilution). An appropriate amount of the solution is removed from the first volumetric flask with a pipette and transferred to a second 250 mL volumetric flask for the second dilution, and the second volumetric flask is filled to the 250 mL mark with internal standard elements and 10% hydrochloric acid, followed by homogenization. Finally, this solution is used for ICP measurement.

[0087] 1.2.Particle size distribution The particle size distribution (PSD) of the positive electrode active material powders is measured by laser diffraction particle size analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory after dispersing each powder sample in an aqueous medium. Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurement.

[0088] 1.3.Polymer cell test 1.3.1. Preparation of polymer cells 1.3.1.1. Preparation of Solid Polymer Electrolyte (SPE) A solid polymer electrolyte (SPE) is prepared according to the following method.

[0089] Step 1) Polyethylene oxide (PEO, 1,000,000 g / mol, Alfa Aesar) and lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI, >98.0%, TCI) are mixed in 99.8 wt% anhydrous acetonitrile (Aldrich) using a mixer at 2000 revolutions per minute (rpm) for 30 minutes. The mass ratio of polyethylene oxide to LiTFSI is 3.0.

[0090] Step 2) Pour the mixture from step 1) into a Teflon dish and dry at 25° C. for 12 hours.

[0091] Step 3) Remove the dried SPE from the dish and punch out the dried SPE to obtain an SPE disk with a thickness of 300 μm and a diameter of 19 mm.

[0092] 1.3.1.2. Preparation of the Positive Electrode The positive electrode is prepared according to the following process.

[0093] Step 1) Prepare a polymer electrolyte mixture containing a solution of polyethylene oxide (PEO, 100,000 g / mol, Alfa Aesar) in 99.7 wt% anhydrous anisole (Sigma-Aldrich) and lithium bis(trifluoromethanesulfonyl)imide salt (LiTFSI, >98.0%, TCI) in acetonitrile. The mixture has a weight ratio of PEO:LiTFSI of 74:26.

[0094] Step 2) The polymer electrolyte mixture prepared in step 1), the positive electrode active material, and the conductive powder (Super P, Timcal) are mixed in an acetonitrile solution in a weight ratio of 21:75:4 to prepare a slurry mixture. The mixture is mixed with a homogenizer at 5000 rpm for 45 minutes.

[0095] Step 3) Cast the slurry mixture from step 2) onto one side of a 20 μm thick aluminum foil with a coater gap of 100 μm.

[0096] Step 4) The foil on which the slurry was cast is dried at 30° C. for 12 hours and then punched out to obtain catholyte electrodes with a diameter of 14 mm.

[0097] 1.3.1.3. Preparation of the negative electrode A Li foil (diameter 16 mm, thickness 500 μm) is prepared as the negative electrode.

[0098] 1.3.1.4. Polymer cell assembly Assemble a coin-shaped polymer cell in an argon-filled glove box from bottom to top with the following components: 2032 coin cell can, positive electrode prepared from section 1.3.1.2, SPE prepared from section 1.3.1.1, gasket, negative electrode prepared from section 1.3.1.3, spacer, wave spring, and cell cap. The coin cell is then completely sealed to prevent electrolyte leakage.

[0099] Test Method Each coin polymer cell is cycled at 80° C. using a Toscat-3100 computer-controlled constant current cycling station (Toyo Systems). The coin cell test procedure uses a 1C current definition of 160 mA / g in the metal window range of ≧3.0 V / Li to ≦4.4 V / Li according to the following schedule:

[0100] Step 1) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V, followed by a 10 minute rest.

[0101] Step 2) Discharge in constant current mode at a C rate of 0.05 with an end condition of 3.0 V, followed by a 10 minute rest. The discharge capacity of this step is DQ1.

[0102] Step 3) Charge in constant current mode at a C rate of 0.05 with an end condition of 4.4V.

[0103] Step 4) Switch to constant voltage mode and maintain 4.4V for 60 hours.

[0104] Step 5) Discharge in constant current mode at a C rate of 0.05 with a termination condition of 3.0 V. The discharge capacity of this step is DQ2.

[0105] Q total Q is defined as the total leakage capacity at high voltage and temperature in step 4) of the described test method. total A small value of indicates that the positive electrode active material powder has high stability during high temperature operation.

[0106] Retention is

number

[0107] 1.4.X-ray photoelectron spectroscopy (XPS) In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.

[0108] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer. Monochromatic Al Kα radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. A broad survey scan to identify the elements present on the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection. Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.

[0109] Curve fitting is performed in CasaXPS version 2.3.19PR1.0 using Shirley-type background processing and Scofield sensitivity coefficients, with fitting parameters according to Table 2a.

[0110] The lineshape GL(30) is the Gaussian / Lorentzian product formula for the 70% Gaussian and 30% Lorentzian lines. LA(α,β,m) is the asymmetric lineshape, where α and β define the tail broadening and m defines the width of the peak.

[0111] [Table 1]

[0112] For the Al and Co peaks, limits are set for the respective defined peaks according to Table 2b. All relevant Ni3p peaks are not quantified.

[0113] [Table 2]

[0114] The surface content of Al and F as determined by XPS is expressed as the atomic fraction of Al and F, respectively, in the surface layer of a particle divided by the combined content of Ni, Mn, and Co in that surface layer, and is calculated as follows:

[0115]

number

[0116]

number

[0117] 1.5. Carbon Analysis The carbon content of the cathode active material powder is measured by a Horiba Emia-Expert carbon / sulfur analyzer. 1 g of the cathode active material powder is placed in a ceramic crucible in a high-frequency induction furnace. 1.5 g of tungsten and 0.2 g of tin as promoters are added into the crucible. The powder is heated at a programmable temperature where the gases produced during combustion are then analyzed by an infrared detector. The carbon concentration is determined by analysis of CO2 and CO.

[0118] 2. Examples and Comparative Examples Comparative Example 1 A single crystal positive electrode active material designated as CEX (Comparative) 1 was prepared according to the following steps.

[0119] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.63 Mn 0.22 Co 0.15 Nickel-based transition metal oxide hydroxide powder (TMH1) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0120] Step 2) First Mixing: TMH1 prepared in step 1) was mixed with Li2CO3 in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Mn, and Co) ratio of 0.85.

[0121] Step 3) First heating: The first mixture from step 2) was heated at 900° C. for 10 hours under dry air atmosphere to obtain a first heating cake.

[0122] Step 4) Second Mixing: The first cooked cake from step 3) was mixed with LiOH in an industrial blender to obtain a second mixture with a lithium to metal (Ni, Mn, and Co) ratio of 1.05.

[0123] Step 5) Second heating: The second mixture from step 4) was heated at 950°C for 10 hours under dry air atmosphere, followed by wet milling, drying and sieving to obtain a second heating product.

[0124] Step 6) Third Mixing: The second heating product from step 5) was mixed with 2 mol% Co from CO3O4 and 5 mol% Li from LiOH, relative to the total atomic contents of Ni, Mn, and Co, respectively, to obtain a third mixture.

[0125] Step 7) Third Heating: The third mixture from step 6) was heated at 775°C for 12 hours under dry air atmosphere to obtain CEX1 containing Ni, Mn, and Co with a Ni:Mn:Co ratio of 0.61:0.22:0.17 by ICP-OES. CEX1 has a D50 of 7 μm.

[0126] After wet milling in step 5), CEX1 is a single crystal powder.

[0127] Example 1 A single crystalline positive electrode active material designated EX(Example) 1 was prepared according to the following steps.

[0128] Step 1) Mixing: CEX1 was mixed with 3000 ppm of PTFE and 2000 ppm of alumina nanopowder in a mixer.

[0129] Step 2) Heating: The mixture obtained from step 1) was heated at 250° C. for 6 hours under oxygen atmosphere, followed by milling to obtain EX1.

[0130] Comparative Example 2 A single crystalline active cathode material, designated CEX2.1, was prepared according to the following steps.

[0131] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.86 Mn 0.07 Co 0.07Nickel-based transition metal oxide hydroxide powder (TMH2) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0132] Step 2) Oxidation of the precursor: The TMH2 prepared in step 1) was heated at 400° C. for 7 hours under an oxidizing atmosphere to obtain a heating product.

[0133] Step 3) First Mixing: The heating product prepared in step 2) was mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Mn, and Co) ratio of 0.96.

[0134] Step 4) First heating: The first mixture from step 3) was heated at 890° C. for 11 hours under an oxidizing atmosphere to obtain a first heating product.

[0135] Step 5) Wet bead milling: The first heating product from step 4) was bead milled in a solution containing 0.5 mol% Co with respect to the total atomic content of Ni, Mn, and Co in the first heating product, followed by drying and sieving to obtain a milled product. The weight ratio of solid to solution for bead milling was 6:4 and was carried out for 20 minutes.

[0136] Step 6) Second blending: The milled product obtained from step 5) was blended in an industrial blender with 1.5 mol % Co from CO3O4, 0.25 mol % Zr from ZrO2, and 7.5 mol % Li from LiOH, each relative to the total atomic content of Ni, Mn, and Co in the milled product, to obtain a second blend.

[0137] Step 7) Second Heating: The second mixture from step 6) was heated at 760°C for 10 hours under oxidizing atmosphere, followed by grinding and sieving with 500 ppm Al from alumina (Al2O3) powder. The final product has CEX2.1, which contains Ni, Mn, and Co with Ni:Mn:Co ratio of 0.84:0.07:0.09 by ICP-OES. CEX2.1 has a D50 of 4μm.

[0138] A single crystalline active cathode material, designated CEX2.2, was prepared according to the following steps.

[0139] Step 1) Mixing: CEX2.1 was mixed with 3000 ppm PVDF and 2000 ppm alumina nanopowder in a mixer.

[0140] Step 2) Heating: The mixture obtained from step 1) was heated at 350° C. for 6 hours under oxygen atmosphere, followed by milling to obtain CEX2.2.

[0141] CEX2.3 was prepared following the same method as CEX2.2, except that PTFE was used instead of PVDF in step 1).

[0142] CEX2.4 was prepared following the same method as CEX2.2, except that PTFE was used instead of PVDF in step 1) and heated at 450 °C in step 2).

[0143] Example 2 A single crystalline active cathode material, designated EX2.1, was prepared according to the following steps.

[0144] Step 1) Mixing: CEX2.1 was mixed with 3000 ppm PVDF and 2000 ppm alumina nanopowder in a mixer.

[0145] Step 2) Heating: The mixture obtained from step 1) was heated at 200° C. for 6 hours under oxygen atmosphere, followed by milling to obtain EX2.1.

[0146] EX2.2 was prepared according to the same method as EX2.1, except that the heating temperature in step 2) was 250°C.

[0147] EX2.3 was prepared according to the same method as EX2.1, except that the heating temperature in step 2) was 300°C.

[0148] EX2.4 was prepared following the same method as EX2.1, except that no alumina was added in step 1) and PTFE was used instead of PVDF, and no heating was performed in step 2).

[0149] EX2.5 was prepared following the same method as EX2.1, except that no alumina was added in step 1) and PTFE was used instead of PVDF, and it was heated at 250°C in step 2).

[0150] EX2.6 was prepared following the same method as EX2.1, except that PTFE was used instead of PVDF in step 1) and no heating was performed in step 2).

[0151] EX2.7 was prepared following the same method as EX2.1, except that PTFE was used instead of PVDF in step 1).

[0152] EX2.8 was prepared following the same method as EX2.1, except that PTFE was used instead of PVDF in step 1) and heated at 250 °C in step 2).

[0153] EX2.9 was prepared following the same method as EX2.1, except that PTFE was used instead of PVDF in step 1) and heated at 300 °C in step 2).

[0154] Comparative Example 3 A single crystalline positive electrode active material, designated as CEX3, was prepared according to the following steps.

[0155] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.90 Mn 0.05 Co 0.05 Nickel-based transition metal oxide hydroxide powder (TMH3) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0156] Step 2) First Mixing: The TMH3 prepared in step 1) was mixed with LiOH and ZrO2 in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Mn, and Co) ratio of 0.99 and 1000 ppm Zr.

[0157] Step 3) First heating: The first mixture from step 2) was heated at 890° C. for 11 hours under an oxidizing atmosphere to obtain a first heating product.

[0158] Step 4) Wet bead milling: The first heating product from step 3) was bead milled in a solution containing 0.5 mol% Co with respect to the total atomic content of Ni, Mn, and Co in the first heating product, followed by drying and sieving to obtain a milled product. The weight ratio of solid to solution for bead milling was 6:4 and was carried out for 20 minutes.

[0159] Step 5) Second blending: The milled product obtained from step 4) was blended in an industrial blender with 1.5 mol % Co from CO3O4 and 1000 ppm Zr from ZrO2, relative to the total atomic content of Ni, Mn, and Co in the milled product, to obtain a second blend.

[0160] Step 6) Second Heating: The second mixture from step 5) was heated at 760°C for 12 hours under oxidizing atmosphere, followed by grinding and sieving with 500 ppm Al from alumina (Al2O3) powder. The product has CEX3, which contains Ni, Mn, and Co with Ni:Mn:Co ratio of 0.88:0.05:0.07 by ICP-OES. CEX3 has D50 of 4μm.

[0161] Example 3 A single crystalline active cathode material, designated EX3, was prepared according to the following steps.

[0162] Step 1) Mixing: CEX3 was mixed with 3000 ppm of PTFE and 2000 ppm of alumina nanopowder in a mixer.

[0163] Step 2) Heating: The mixture obtained from step 1) was heated at 250° C. for 6 hours under oxygen atmosphere, followed by milling to obtain EX3.

[0164] Comparative Example 4 A polycrystalline positive electrode active material, designated as CEX4, was prepared according to the following steps.

[0165] Step 1) Preparation of transition metal oxide hydroxide precursor: Metal composition Ni 0.83 Mn 0.12 Co 0.05 Nickel-based transition metal oxide hydroxide powder (TMH4) with the above formula was prepared by co-precipitation process in a large-scale continuous stirred tank reactor (CSTR) containing mixed nickel manganese cobalt sulfate, sodium hydroxide, and ammonia.

[0166] Step 2) First Mixing: The TMH4 prepared in step 1) was mixed with LiOH in an industrial blender to obtain a first mixture with a lithium to metal (Ni, Mn, and Co) ratio of 0.975.

[0167] Step 3) First heating: The first mixture from step 2) was heated at 765° C. for 10 hours under an oxidizing atmosphere to obtain a first heating product, which was then crushed and sieved.

[0168] Step 4) Second mixing: The first heating product from step 3) and LiOH as lithium source were homogeneously mixed in an industrial blending device with a lithium to metal (Ni, Mn, and Co) ratio of 1.03 to obtain a second mixture.

[0169] Step 5) Second Heating: The second mixture from step 4) was heated at 770° C. for 12 hours under oxygen atmosphere to obtain CEX4 containing Ni, Mn, and Co with a Ni:Mn:Co ratio of 0.83:0.12:0.05 by ICP-OES. CEX4 has a D50 of 6 μm.

[0170] Example 4 A polycrystalline active cathode material designated EX4.1 was prepared according to the following steps.

[0171] Step 1) Mixing: CEX4 was mixed with 2000 ppm of PTFE and 2000 ppm of alumina nanopowder in a mixer.

[0172] Step 2) Heating: The mixture obtained from step 1) was heated at 250° C. for 6 hours under oxygen atmosphere, followed by milling to obtain EX4.1.

[0173] EX4.2 was prepared according to EX4.1, except that in step 1) 3000 ppm of PTFE was used.

[0174] EX4.3 was prepared according to EX4.1, except that in step 1) 4000 ppm of PTFE was used.

[0175] [Table 3]

[0176] Table 2 summarizes the compositions of the examples and comparative examples and their corresponding electrochemical properties.

[0177] CEX1 and EX1 are single crystal positive electrode active materials containing approximately 61 mol% Ni. EX1, which further contains F and Al, has a higher Q than CEX1. total This results in lowering of creatine phosphate ...

[0178] CEX2.1 to CEX2.5 and EX2.1 to EX2.9 are single crystal positive electrode active materials containing about 84 mol% Ni. CEX2.1 is a positive electrode active material that does not contain F. CEX2.2 to CEX2.4 are mixtures of CEX2.1 and an F-containing polymer, either PVDF or PTFE, which are heated to a temperature of ≧350° C. Such heat treatment results in the formation of a Q total It can be seen that positive electrode active materials with high carbon content and low retention are obtained. Due to the low carbon content of less than 350 ppm, the F-containing polymer is likely to decompose at temperatures ≧350° C. On the other hand, EX2.1 to EX2.9 are heat-treated at temperatures ≦300° C. All the examples show improved electrochemical properties compared to CEX2.1 to CEX2.4.

[0179] CEX3 and EX3 are single crystal cathode active materials containing approximately 88 mol% Ni. EX3, which contains F and Al, has improved electrochemical properties compared to CEX3.

[0180] CEX4 and EX4.1-EX4.3 are polycrystalline cathode active materials containing approximately 88 mol% Ni. EX4.1-EX4.3 are derived from CEX4 mixed with alumina, various amounts of PTFE, and heated at 250° C. EX4 is shown to exhibit lower Qtotal and higher retention compared to CEX4.

[0181] Table 2 also summarizes the XPS analysis results for CEX2.3, CEX2.4, EX2.6, EX2.7, EX2.8, and EX2.9 showing the Al and F fractions relative to the total atomic fractions of Ni, Mn, and Co. Values ​​greater than 0 indicate the presence of Al or F at the surface of the positive electrode active material, in relation to XPS measurements that acquire signals from the very top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer.

[0182] It is concluded that the positive electrode active material containing F and C is suitable for meeting the objectives of the present invention, i.e., low total leakage capacity (Q total ) and high retention, providing a positive electrode active material with good electrochemical properties.

Claims

1. A positive electrode active material for a solid-state rechargeable battery comprising lithium, oxygen, nickel, and at least one metal selected from the group consisting of manganese and cobalt, fluorine, wherein the atomic ratio of F to the total amount of Ni, Mn, and / or Co is ≧0.05 and ≦3.0 as determined by XPS analysis; 13. A cathode active material, further comprising: carbon, the carbon content being 370 ppm or more and 5000 ppm or less, based on a total weight of the cathode active material, as determined by a carbon analyzer.

2. 2. The cathode active material of claim 1, wherein the cathode active material has an atomic ratio of F to the total amount of Ni, Mn, and / or Co of 0.1 or more and 2.5 or less, as determined by XPS analysis.

3. 10. The active cathode material of claim 1, wherein the active cathode material comprises carbon having a carbon content greater than 500 ppm and less than 3000 ppm as determined by a carbon analyzer.

4. 2. The cathode active material of claim 1, comprising aluminum, the atomic ratio of Al to the total amount of Ni, Mn, and / or Co being 0.2 or more and 4.0 or less as determined by XPS analysis.

5. 2. The cathode active material of claim 1, comprising aluminum in an amount of 0.01 mol% to 2.0 mol%, preferably 0.05 mol% to 1.5 mol%, based on the total atomic content of Ni, Mn, and Co in the material as determined by ICP-OES.

6. 2. The cathode active material of claim 1, wherein the cathode active material has an atomic content of nickel of 55.0 mol % to 95.0 mol %, preferably 58.0 mol % to 90.0 mol %, based on the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

7. 2. The cathode active material of claim 1, wherein the cathode active material has an atomic content of cobalt of 0 mol % to 40.0 mol %, preferably 2.0 mol % to 20.0 mol %, based on the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

8. 2. The cathode active material of claim 1, wherein the cathode active material has an atomic content of manganese of 0 mol % or more and 40.0 mol % or less, preferably 2.0 mol % or more and 30.0 mol % or less, relative to the total atomic content of Ni, Mn, and Co in the material, as determined by ICP-OES.

9. The cathode active material of claim 1 , wherein the cathode active material comprises single crystal particles.

10. The particles have a median particle size D50 of 2.0 μm or more and 10.0 μm or less as determined by laser diffraction particle size analysis. A The positive electrode active material according to claim 9 .

11. The cathode active material of claim 1 , wherein the cathode active material comprises polycrystalline particles.

12. The particles have a median particle size D50 of 2.0 μm or more and 10.0 μm or less as determined by laser diffraction particle size analysis. A The positive electrode active material according to claim 11 ,

13. A method for producing a positive electrode active material, comprising: Mixing a lithium transition metal based oxide compound and an F-containing polymer; heating the mixture at a temperature less than 350° C. in an oxidizing atmosphere in a furnace for a time period of at least 1 hour and not more than 20 hours to obtain the cathode active material.

14. The method of claim 13, wherein the F-containing polymer is polyvinylidene fluoride or polytetrafluoroethylene.

15. The method according to claim 13 or 14, wherein the heating temperature is from 200° C. to 350° C., preferably from 250° C. to 300° C.

16. The method of claim 13, wherein the positive electrode active material is according to any one of claims 1 to 9.

17. A solid-state battery comprising the positive electrode active material according to any one of claims 1 to 12.

18. 20. Use of the solid-state rechargeable battery of claim 17 in any one of a portable computer, a tablet, a mobile phone, an energy storage system, an electric vehicle, or a hybrid vehicle.

Citation Information

Patent Citations

  • Method for manufacturing a cathode active material for a secondary battery, the cathode active material manufactured in this manner, and a lithium secondary battery including the same

    JP2020529716A

  • Method of manufacturing lithium nickel complex oxide, lithium nickel complex oxide manufactured thereby, and cathode active material including the same

    US20150064563A1

  • Lithium nickel-manganese-cobalt oxide cathode powders for high voltage lithium-ion batteries

    WO2016116862A1